Evaluasi Dampak Pembangunan Sosial, Bagi Kesejahteraan Masyarakat Kabupaten Purbalingga - Sri Murni Setyawati; Irma Suryahani (EKO-REGIONAL, 2007)
This research evaluation is a part of activities development management is to know how the activities development works.  Evaluation could be good or bad is depended on the inputs of the monitoring systems. This research is analysed by indicator descriptions.  The conclusion shows that Purbalingga’s PDRB in 2003 increase about 1.3%.  In other side, the gaps among sectors are low enough.  It means each sector works better and relatively will be spread evenly.  That’s why the policy of budget allocation is better to lead to have interrelatedness (backward and forward) for all sectors.Keywords: monitoring systems, Indicator description, budget allocation.